1999
DOI: 10.1159/000026578
|View full text |Cite
|
Sign up to set email alerts
|

Contingent Negative Variation and Attention in Schizophrenic and Depressed Patients

Abstract: Contingent negative variation (CNV) is supposed to be a psychophysiological indicator of attention and arousal. Both have been reported to be deteriorated in schizophrenic and depressed patients. Thirty-four patients with major depression, 43 patients with schizophrenia and 49 healthy subjects were investigated during acute illness with a complex three-stimulus go/no-go task which requires different states of attention: trials consisted of three complex figures that were tachistoscopically presented. Three ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…106,107 While healthy controls generally show a larger component during antisaccades relative to prosaccades, patients fail to show this augmentation and have smaller components in general. 108-110 Deficits in contingent negative variation are not specific to schizophrenia (e.g., depression; 111 ADHD 112 ). More research is needed to understand the reliability of both EEG measures in relation to AS performance, their state-dependence, and impairments in biological relatives.…”
Section: Antisaccade Taskmentioning
confidence: 99%
“…106,107 While healthy controls generally show a larger component during antisaccades relative to prosaccades, patients fail to show this augmentation and have smaller components in general. 108-110 Deficits in contingent negative variation are not specific to schizophrenia (e.g., depression; 111 ADHD 112 ). More research is needed to understand the reliability of both EEG measures in relation to AS performance, their state-dependence, and impairments in biological relatives.…”
Section: Antisaccade Taskmentioning
confidence: 99%
“…An earlier study from West, Choi, and Travers (2010) observed that negative affect (measured using a Beck Depression Inventory) in healthy individuals was associated with attenuated proactive and reactive cognitive control (using a counting Stroop task). Moreover in clinically depressed patients, an abnormal contingent negative variation (CNV) during the engagement of preparatory processes has been observed (Ashton, Marshall, Hassanyeh, Marsh, & Wright-Honari, 1994; Heimberg et al, 1999; Giedke & Heimann, 1987). This slow cue-locked cortical potential, which is maximal over frontocentral sites, reflects anticipatory attention and effortful processing (Brunia & van Boxtel, 2001).…”
mentioning
confidence: 99%
“…This would mean that a similar amount of attentional resources has been allocated to the processing of the context prime words. However, against this prediction, it has to be noted that early CNVs generally appear to be smaller in schizophrenia patients than in normals (e.g., Verleger et al, 1999;Heimberg et al, 1999). Nevertheless, in the first study S1 was presented for a relatively brief duration (200 ms), whereas, in the second study, it consisted of previously unknown and complex figures, which were thus difficult to process.…”
Section: Context Processing In Schizophreniamentioning
confidence: 97%
“…Thus, no predictions were made as to these components for the chosen protocol. However, it should be noted that the late CNV appears to be of smaller amplitude in patients than in normals (e.g., (Verleger et al, 1999;Heimberg et al, 1999).…”
Section: Context Processing In Schizophreniamentioning
confidence: 99%